CYP1A1 T3801 C polymorphism and lung cancer: A pooled analysis of 2,451 cases and 3,358 controls - Paolo Vineis; Fabrizio Veglia; Simone Benhamou; Dorota Butkiewicz; Ingolf Cascorbi; Margie L. Clapper; Vita Dolžan; Aage Haugen; Ari Hirvonen; Magnus Ingelman‐Sundberg; Masahiro Kihara; Chikako Kiyohara; et al. (2003)
Abstract CYP1A1 is involved in the metabolism of benzopyrene, a suspected lung carcinogen; it is therefore conceivable that genetically determined variations in its activity modify individual susceptibility to lung cancer. The role of the CYP1A1 MspI polymorphism in lung cancer has been widely studied but has not been fully clarified. We have included 2,451 cases and 3,358 controls in a pooled analysis of 22 case‐control studies on CYP1A1 and lung cancer risk. We found a clear association between the CYP1A1 homozygous MspI restriction fragment length polymorphism (RFLP) and lung cancer risk in Caucasians (age‐ and gender‐adjusted odds ratio = 2.36; 95% confidence interval 1.16–4.81); other associations were weaker or not statistically significant. The association with the homozygous variant was equally strong for squamous cell carcinomas and adenocarcinomas among Caucasians. We analyzed the risk by duration of smoking: for Caucasian subjects with the MspI RFLP combined variants (homozygotes plus heterozygotes), the increase in the risk of lung cancer was steeper than among the individuals with the homozygous reference allele. Our analysis suggests that Caucasians with homozygous variant CYP1A1 polymorphism have a higher risk of lung cancer. The data were more consistent among Caucasians, with a strong association between the homozygous variant in both squamous cell carcinomas and adenocarcinomas, and a stronger association in men than in women. The analyses were more inconsistent and failed to reach statistical significance in Asians. This observation might be due to design specificities or unknown effect modifiers in the Asian studies. © 2003 Wiley‐Liss, Inc.